Measurement of Awareness among Consumers Regarding Patanjali Products: An examination of consumer awareness and attitudes towards Patanjali products (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today, worldwide, the Patanjli Brand is synonymous with safe and efficacious health care. Science and research lie at the heart of product development. Although our scientists have studied more than 10,000 herbs and developed a range of over300 products, we continue on our journey to unravel the mysteries of nature. Patanjali have been used as medicines for a long time. Currently, it is still utilized as important ingredients of a few consumer products including cosmetic products. The study is based on consumer attitudes towards the Patanjali Products with sample size of 150. It was found from the study that majority of the Consumers are aware about the Patanjali products.